ERADICATION OF CRIMINAL ACTS OF CORRUPTION TOWARDS DIRECTORS OF COMMANDITAIRE VENNOOTSCHAP WHO PERFORM CRIMINAL ACTS OF CORRUPTION - Sibghatullah BW, As'ad Djaelani (Awang Long Law Review, 2023)
This study aims to determine and to qualify criminal acts of corruption within article 2 and article 3 of Law Number 31 Year 1999 On Eradication of Criminal Acts of Corruption, and to determine the application of material criminal law and legal considerations by the judges in deciding the verdict The statute approach, which examines laws that are related to research problems, is the approach used in this normative research. In addition to the statue approach, the author also carries out a case approach, which means that this research is complemented by a review of the judge's considerations in the decision. The primary and secondary materials obtained were then analyzed descriptively to then be presented qualitatively. This research concluded that: 1) Article 2 and Article 3 of the Law of 1999 has several differences. One of the differences can be found on the subject. Article 2 applies to anyone who commits the act and Article 3 applies to anyone with a "post or position" who abuses the authority in committing the act. This means the subject of Article 3 only refers to Civil Servants; and 2) the application of material law against the CV Director who committed the criminal act of corruption is improper due to the facts that the defendant as a CV director is not considered as a Civil Servant and the judge consideration sentenced the defendant with subsidiary indictment ( Article 3) because according to the judges his action fulfills the materials of the article.